THE INFLUENCE OF MOTIVATION AND LEADERSHIP STYLE ON THE PERFORMANCE OF TEBING TINGGI DISPORA EMPLOYEES (Case Study on Contract Employees of the Youth and Sports Service in Pematang Siantar City) - Hafnida Ritonga, Sri; Panjaitan, Hadi; Mayanta Tarigan, Hendri; Karo Karo, Romaida; Aulia Nanda, Ficha (Universitas Efarina, 2022)
This study aims to find out how the influence of motivation and leadership style on the performance of Pematang Siantar Dispora employees. The research method used is the method of qualitative data and quantitative data. While the data used is primary data. 1) obtained a tcount value of 1.482 With α = 5%, ttable (5%; 31-2=29) obtained a ttable value of 2.045 From this description it can be seen that tcount (1.482) < ttable (2.045), as well as the significance value by 0,14> 0.05 it can be concluded hypothesisfirst denied, meaningMotivation Variable (X1) is not significant to Employee Performance Variable (Y). 2)tcount value is obtained3,433With α = 5%, ttable (5%; 31-2 = 29) obtained a ttable value of 2.045 From this description it can be seen that tcount (3,433) > ttable (2.045), and a significance value of 0.00 <0.05, it can be concluded that the second hypothesis is accepted, meaningLeadership Style Variable (X2) has a positive and significant effecton Employee Performance Variable (Y). 3) the value of Fcount is obtained29,335With α = 5%, dk quantifier: 3, dk denominator: 31-2-1 (5%; 2; 28) the Ftable value is 3.34. From this description it can be seen that Fcount (29,335) > Ftable (3.34), and a significance value of 0,00< 0.05, it can be concluded that the third hypothesis is accepted, meaning Motivation Variable (X1), Leadership Style Variable (X2) have a positive and significant simultaneous effect on Employee Performance Variable (Y).